Tourism Village Development Strategy Through The Community Based Tourism Concept In Ciliang Village, Parigi District, Pangandaran Regency - Jauhari, Regitha; Novianti, Evi; Endyana, Cipta (GoAcademica Research & Publishing, 2024)
Ciliang Village has tourism potential, namely nature, culture, and cuisine. One of the famous there is Batu Hiu Beach. However, this potential has not been explored optimally, as can be seen from the status of the developing village index in 2022 which still has the title